2018
DOI: 10.1002/pro.3374
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and evolution of the hemerythrin‐like domain superfamily

Abstract: Hemerythrin-like proteins have generally been studied for their ability to reversibly bind oxygen through their binuclear nonheme iron centers. However, in recent years, it has become increasingly evident that some members of the hemerythrin-like superfamily also participate in many other biological processes. For instance, the binuclear nonheme iron site of YtfE, a hemerythrin-like protein involved in the repair of iron centers in Escherichia coli, catalyzes the reduction of nitric oxide to nitrous oxide, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…native proteins are comprised of six or eight of these subunits [8,9] although a bacterial hemerythrin has been identified that is a monomer [10]. The other HLPs with different iron ligation patterns and different biological functions possess additional domains on each protein that are required for their respective biological functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…native proteins are comprised of six or eight of these subunits [8,9] although a bacterial hemerythrin has been identified that is a monomer [10]. The other HLPs with different iron ligation patterns and different biological functions possess additional domains on each protein that are required for their respective biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins typically are comprised of identical subunits of four α-helices, with each subunit housing a di-iron site with a bridging oxygen. The proteins typically possess six or eight of these subunits [8,9], although monomeric hemerythrins have been identified in the bacterium Methylococcus capsulatus [10] and the peanut worm Themiste hennahi [11]. The recombinant Rv2633c protein that was expressed in Escherichia coli and purified [7] was a homodimer that contained two iron ions per subunit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemerythrin-like proteins are also found in bacteria, archaea and some eukaryotic groups including humans; however, their functions are not clear. They are proposed to be oxygen or iron sensors, oxygen carriers, or to act as protectors under oxidative stress conditions ( Alvarez-Carreño et al, 2018 ). Also, among the proteins that were considerably upregulated under excessive copper we found two homologs of a heme-containing protein, protoglobin.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Some HLPs possess the same sequence motif as hemerythrin, while others have HHEHHE or HHEEHHE motifs. 4 In contrast to these motifs, the sequence motif in the mycobacterial HLPs proteins is HHEYHHE. 2 These are the only group of HLPs that utilize a Tyr as an iron ligand.…”
Section: Introductionmentioning
confidence: 99%